Poly-Lactic Acid-Based Biopolymer Formulations Are Safe for Sustained Intratympanic Dexamethasone Delivery. Issue 7 (August 2019) - Rousset, Francis; Kokje, Vivianne Beatrix Christina; Coelho, Marta Da Costa; Mugnier, Thibault; Belissa, Emilie; Gabriel, Doris; Gurny, Robert; Krause, Karl Heinz; Senn, Pascal
Abstract : Hypothesis and Background: The clinical treatment of sudden sensorineural hearing loss currently relies on the administration of steroids, either systemically or via intratympanic injections. Intratympanic injections bypass the hemato-cochlear barrier, reducing its systemic side effects. The efficacy of the injections is limited through rapid drug clearance via the Eustachian tube, and through nonoptimal properties of slow-release drug carriers. A new slow-release drug delivery vehicle based on hexyl-substituted-poly-lactic-acid (HexPLA), with the highest possible safety profile and complete bio-degradability, has been evaluated for safety and efficacy in a standardized guinea pig model of intratympanic injection. Methods: A total of 83 animals received through retrobullar injection either empty Nile-red-colored HexPLA vehicle, 5%-dexamethasone-HexPLA, 5%-dexamethasone suspension, or a sham operation. Long-term residence time of vehicle, biocompatibility, click- and pure-tone hearing thresholds, and dexamethasone levels in the perilymph were prospectively assessed. Results: At 1 week after injection, HexPLA vehicle was morphologically present in the middle ear and perilymph levels in the 5%-dexamethasone-HexPLA were on average 2 to 3 μg/ml and one order of magnitude higher compared with those of the 5%-dexamethasone suspension group. No significant postoperative morphological or functional changes were observed up to 3 months postdelivery. Conclusions: HexPLA is safe, fully biocompatible, and efficient for sustained high-dose, intratympanic delivery of dexamethasone at least for 1 week and therefore of high interest for the treatment of sudden sensorineural hearing loss and other acute inner ear diseases. Due to the favorable chemical properties, a wide range of other drugs can be loaded into the vehicle further increasing its potential value for otological applications. Abstract : Supplemental Digital Content is available in the text